Effect of Tank Mixed Application of Ammonium Sulphate and Carfentrazone-Ethyl + Clodinafop-Propargyl + Metsulfuron-Methyl on Weeds and Yield of Wheat: Ammonium Sulphate as Adjuvant for Weed Control - Tanveer, Asif; Khalid, Adnan; Tahir, Muhammad; Nadeem, Muhammad Ather (Biological Sciences - PJSIR, 2014)